Neuropsychological aspects in patients with phenylketonuria (PKU) - Carmen Sánchez; Sheribeth Rodríguez- Ríos (Instituto Nacional de Pediatría, 2014)
The evaluation of neuropsychological development in phenylketonuria patients must be considered in a comprehensive follow-up. This assessment should include all aspects of healthy development, including motor skills. This article outlines the results of a study whose objective was to show the relationship between age at onset of dietary treatment and adherence to the treatment, and the motor behavior of hyperphenylalaninemic children under nine years.